On the morphological, biological and genetic heterogeneity of the genus Orchis (Orchidaceae, Orchidinae) - Tyteca, Daniel; Ceinos, Manon; Gathoye, Jean-Louis; Brys, Rein; Jacquemyn, Hans (Phytotaxa, 2012)
Circumscription of Orchis (Orchidaceae, Orchidinae) has undergone many changes in the last few decades. However, delimitation of the genus is still subject to debate. In its present state, Orchis s.str. appears to be composed of two well-differentiated, monophyletic groups of species, now treated as subgenera (Orchis s.s. and Masculae). Here we present detailed morphological measurements of floral and vegetative traits collected for a large number of species of the two subgenera and the related genus Anacamptis to provide further insights in the taxonomy of this genus. Using multivariate analyses, we show that three groups of species are clearly separated morphologically and that this separation is more pronounced between the two subgenera than between Masculae and Anacamptis. This morphological variation is also supported by significant differences in seed micromorphology of the two subgenera. Review of the literature further provided significant differences in pollinator assemblages between the two subgenera, suggesting substantial pre-zygotic reproductive isolation, and a significant difference in diversity of fungal associates with species of the two subgenera, possibly contributing to post-zygotic reproductive isolation. The fact that no viable hybrid between the two subgenera has ever been observed under artificial or natural conditions is in line with these findings. Based on these findings, an appropriate taxonomic rank for the two groups is discussed.